HUBUNGAN PENGETAHUAN DAN SIKAP KARIYAWAN DENGAN TINDAKAN PENANGANAN LIMBAH ARSIP PADAT MEDIS DI PUSKESMAS KARANG TALIWANG - Rizal Sultani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Wahyu Aprilyaningsih (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Solid medical waste poses health risks such as disease transmission. Healthcare workers in hospitals are vulnerable to the risks of medical waste management. This study aims to determine the relationship between knowledge and attitudes of employees with the management actions of solid medical waste at Puskesmas Karang Taliwang. This is a quantitative study with a cross-sectional approach using total sampling method. The number of samples was 42 respondents. There were 54.8% of healthcare workers who had good knowledge, 45.2% had moderate knowledge, and 52.4% of healthcare workers had a good attitude while 61.9% had proper medical waste management actions. The relationship between knowledge of solid medical waste management and healthcare personnel (p 0.037) and the attitude towards solid medical waste management has a relationship with healthcare personnel (p 0.14). Employees have knowledge and attitudes towards the management of solid medical waste. There is a relationship between knowledge and attitude towards the management of solid medical waste and healthcare personnel.